Severe hypoglycemia reduces the shivering threshold in rabbits - Keiichi Wada; Taishi Masamune; Hirofumi Ino; Kenta Ueda; Tadahiko Ishiyama; Daniel I. Sessler; Takashi Matsukawa (BMC Anesthesiology, 2019)
Abstract Background We previously reported that each 100 mg dL− 1 reduction in blood glucose over the range from ≈90 to > 300 mg dL− 1 decreases the shivering threshold (triggering core temperature) in rabbits by 1 °C. However, the effects of lower blood glucose concentrations has yet to be evaluated. We thus evaluated the relationship between the shivering threshold and blood glucose concentration over the mild-to-severe hypoglycemic range. Methods Thirty-nine rabbits were lightly anaesthetized with isoflurane and randomly assigned to one of the three groups: 1) severe hypoglycemia, insulin and dextrose infusions titrated to achieve blood glucose concentration at 45–75 mg dL− 1; 2) mild hypoglycemia, insulin and dextrose infusions titrated to achieve blood glucose concentration at 75–100 mg dL− 1; and 3) saline infusion. Cooling by colonic perfusion of water at 10 °C was continued until shivering occurred or esophageal core temperatures reached to 34 °C. Results The shivering threshold in the severe hypoglycemic rabbits was 35.7 ± 1.1 °C (mean ± SD); the thresholds in the mild hypoglycemic rabbits was 37.0 ± 0.7 °C; and the threshold in the control rabbits was 37.9 ± 1.0 °C. The shivering threshold increased linearly with blood glucose concentration: shivering threshold (°C) = 0.032 ∙ [blood glucose concentration (mg dL− 1)] + 34.1, R2 = 0.45. The shivering threshold thus decreased by approximately 1 °C for each 31 mg dL− 1 decrease in blood glucose concentration. Conclusions There was a linear relationship between blood glucose and the shivering threshold over the range from severe hypoglycemia to normoglycemia. Blood glucose perturbations in the hypoglycemic range reduced the shivering threshold about three times as much as previously reported for the hyperglycemic range.